The pregnancy microbiome and preterm birth - Bayar,E; Bennett,PR; Chan,D; Sykes,L; MacIntyre,D (Springer Seminars in Immunopathology, 2020)
Preterm birth is a global health concern and continues to contribute to substantial neonatal morbidity and mortality despite advances in obstetric and neonatal care. The underlying aetiology is multi-factorial and remains incompletely understood. In this review, the complex interplay between the vaginal microbiome in pregnancy and its association with preterm birth is discussed in depth. Advances in the study of bacteriology and an improved understanding of the human microbiome have seen an improved awareness of the vaginal microbiota in both health and in disease.